2012
DOI: 10.5588/ijtld.11.0414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of the meropenem-clavulanate combination for extensively drug-resistant tuberculosis [Case study]

Abstract: Mycobacterium tuberculosis strains resistant to almost all available anti-tuberculosis drugs are an increasing threat to public health worldwide. Among existing drugs with potential antimycobacterial effects, the combination of meropenem with clavulanate has been shown to have potent in vitro bactericidal activity against extensively drug-resistant tuberculosis (XDR-TB). To explore its potential clinical efficacy, a meropenem-clavulanate-containing salvage regimen was started in six patients with severe pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 9 publications
1
86
0
1
Order By: Relevance
“…␤-Lactam-␤-lactamase inhibitor combinations attract more attention due to their effective in vivo and in vitro activity against MDR-TB strains (9,15,16). The present study showed that different ␤-lactam-␤-lactamase inhibitor combinations vary in their anti-MDR-TB efficiency in vitro.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…␤-Lactam-␤-lactamase inhibitor combinations attract more attention due to their effective in vivo and in vitro activity against MDR-TB strains (9,15,16). The present study showed that different ␤-lactam-␤-lactamase inhibitor combinations vary in their anti-MDR-TB efficiency in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, another ␤-lactam-␤-lactamase inhibitor combination, meropenem-clavulanate, also showed high antimycobacterial activity in vivo against MDR-TB and XDR-TB strains of M. tuberculosis (16). Several clinical trials have provided preliminary evidence of the effectiveness and safety of meropenem-clavulanate in the treatment of MDR-TB and XDR-TB (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, although the experience is still very limited, this carbapenem/clavulanate combination seems to be helpful in the treatment of XDR-TB patients [57][58][59]. In a study by DE LORENZO et al [57], patients treated with meropenem/clavulanate in addition to a linezolid-containing MDR-TB regimen achieved a higher smear conversion rate at 3 months than controls (87.5% versus 56%, p=0.02).…”
Section: Groupmentioning
confidence: 99%
“…Carbapenems have been demonstrated to have modest activity in mouse models of TB (14)(15)(16), which are often problematic due to the sensitivity of carbapenems to degradation by murine dehydropeptidase (17). More importantly, encouraging results have been obtained in case series of XDR-TB patients treated with a combination of meropenem plus clavulanate (18)(19)(20).…”
mentioning
confidence: 99%